Awareness of biomedical waste management among clinical teaching staff in a private medical college in rural area of Maharashtra - Naik, Qais; Vasantrao, Chincholikar Sanjeev; Surendra, Kulkarni (International Journal Of Community Medicine And Public Health, 2019)
Background: Biomedical waste has become a serious health hazard in many countries, including India. The waste produced in the course of health care activities carries a higher potential for infection and injury than any other type of waste. The main aims and objectives of this study are to assess the knowledge, attitude and practices among the clinical teaching staff of a private medical college regarding biomedical waste management. Methods: An observational, cross-sectional study was conducted among the clinical teaching staff of a private medical college regarding biomedical waste management. All the clinical teaching staff members enrolled on the roll muster were included. The data collection was done by interview technique using a pretested, structured questionnaire. Results: Awareness about the number of categories of segregation of biomedical waste was found in 99% of the respondents. However 94% participants among them knew correctly the colour code of segregation but parcentage details of these categories varied from 49% to 90%. Percentage of actual practice of biomedical waste management varied from 57% to 77%. Conclusions: The staff had exemplary knowledge of basic questions like number of categories of BMW segregation; however details of these categories were known to a somewhat fewer people. Awareness was much more in in clinicians who are having experience of less than 5 years. There is a need of organization of seminars to update their knowledge regarding biomedical waste management.